Maintained Improvement of Neurocognitive Function in Major Depressive Disorders 6 Months after ECT - Mohn, Christine; Rund, Bjørn Rishovd (Frontiers in Psychiatry, 2016)
Both impaired and improved cognitive function after electroconvulsive treatment (ECT) in major depressive disorder (MDD) patients may occur. We have previously found improved cognitive function 6 weeks after ECT in this group. The aim of this study was to report 6-month follow-up results from the same prospective project monitoring cognitive effects of ECT. Thirty-one patients with major depressive disorder were assessed with the MATRICS Consensus Cognitive Battery (MCCB), the Everyday Memory Questionnaire (EMQ), and the Montgomery-Åsberg Depression Rating Scale (MADRS) prior to, 6 weeks, and 6 months after ECT. Compared to baseline, the Speed of Processing, Attention/Vigilance, and Reasoning/Problem Solving test results were significantly improved. The depression score was significantly reduced. There were no changes in subjective memory complaint. There were no significant relationship between the EMQ and the MCCB subtests, but a significant correlation between current depression level and the EMQ. Six months after ECT the cognitive improvement reported at 6 weeks follow-up was maintained and extended. The corresponding decrease in depressive symptoms and stability in subjectively reported memory complaints suggests that the antidepressant effects of ECT do not occur at the expense of cognitive function.